2014
DOI: 10.1039/c4ra08872g
|View full text |Cite
|
Sign up to set email alerts
|

Controlled RAFT synthesis of side-chain oleic acid containing polymers and their post-polymerization functionalization

Abstract: We report the synthesis and characterization of well-defined polymers from oleic acid as the bio-renewable resource. Double bonds in oleate side-chains in the polymer are further modified by thiol-ene reaction, epoxidation, and cross-linking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
45
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 39 publications
0
45
0
Order By: Relevance
“…In order to overcome this drawback, some research groups focused on the copolymerization of vegetable oils with a more reactive co‐monomer to provide suitable additives for lubricating oil . However, FA could be also functionalized with (meth)acrylate moieties to overcome their poor reactivity in radical polymerization . For instance, Maiti et al .…”
Section: Introductionmentioning
confidence: 99%
“…In order to overcome this drawback, some research groups focused on the copolymerization of vegetable oils with a more reactive co‐monomer to provide suitable additives for lubricating oil . However, FA could be also functionalized with (meth)acrylate moieties to overcome their poor reactivity in radical polymerization . For instance, Maiti et al .…”
Section: Introductionmentioning
confidence: 99%
“…Methacrylic acid, allyl amine, phenethylamine, and triethylamine were purchased from Merck Chemicals (India). MAEO monomer was synthesized as reported earlier . The RAFT chain‐transfer agent (CTA) 2‐cyanopropan‐2‐yl benzodithioate (CPDB) was synthesized by following the standard literature procedure .…”
Section: Methodsmentioning
confidence: 99%
“…Recently, we have polymerized methacrylate monomer 2‐(methacryloyloxy) ethyl oleate (MAEO) containing oleic acid side chains in a controlled fashion by a reversible addition–fragmentation chain‐transfer (RAFT) process. The C=C double bond in oleate side chains of the homopolymer (PMAEO) reacted with various organic thiol compounds in a thermally initiated thiol‐ene reaction . Post‐polymerization functionalization of polymers bearing dual‐functional reactive units in a sequential one‐pot reaction could be an important method for creating single‐reactive polymers to generate a diverse library of functional polymers.…”
Section: Introductionmentioning
confidence: 99%
“…Then, the vial was put in a preheated reaction block, which was already set at 60 °C for 10 h. Polymerization reaction was quenched by cooling the vial in ice‐water bath, and the polymer was purified by reprecipitation in MeOH at least five times (from acetone solution) and dried under high vacuum at room temperature to obtain a yellowish sticky material. The average degree of polymerization (DP n ) for this PMAEO macroCTA has been calculated as 14 via 1 H NMR spectroscopy by comparing the signal integration ratio of oxyethylene protons (4H) of PMAEO repeating units at 4.03–4.39 ppm to the chain end peak from CDP moiety at 2.5 ppm …”
Section: Methodsmentioning
confidence: 99%
“…In our earlier report, we showed that the oleic acid derived methacrylate monomer (having one chemoselective pendant double bond) was dormant during the RAFT polymerization and molecular weight control was obtained up to ∼30,000 g/mol. Double bonds in oleate side‐chains in the polymer were reactive under some specific post‐polymerization conditions to afford a set of functionalized polymers with well‐defined macromolecular characteristics . With this knowledge of RAFT tolerance of oleate moiety, herein we prepared its corresponding homopolymer of definite chain length (macroCTA), and exploited as steric stabilizer for non‐polar RAFTDP of BzMA.…”
Section: Introductionmentioning
confidence: 99%